Biological control of the coffee berry borer with entomopathogenous fungi in Nayarit, Mexico - Sánchez-Lucio, Roberto; González-Gaona, Ernesto; Gómez-Jaimes, Rafael; De Lira-Ramos, Karla Vanessa; Gallegos-Robles, Miguel Ángel; García-Hernández, José Luis; Padilla-Ramírez, José Saúl (Ecosistemas y Recursos Agropecuarios, 2024)
The berry borer is the most damaging insect pest of coffee worldwide, affecting both yield and quality. Due to its economic importance, the borer has been the subject of considerably research around the world, both to determine its biology, as well as to develop economically and environmentally viable control technologies. Much of the work has focused on biological control with parasitoids and entomopathogens. The objective of this study was to isolate, identify and evaluate strains of Beauveria bassiana native to the coffee growing areas of Nayarit against the coffee berry borer under field conditions. The strains were obtained from soil and coffee fruit samples from 15 coffee orchards and were evaluated in an organic coffee production orchard. In general, the strains of B. bassiana showed good performance against the coffee berry borer with effectiveness higher than 76%. In the region of study, if control measures are not applied, the percentages of infestation could reach up to 56%. Regional B. bassiana strains are considered an option for biological control of the coffee berry borer.
Keywords: Biological effectiveness; Incidence; Severity; B. bassiana